The Lyon Terence : Its Tradition and Legacy - Torello-Hill, Giulia (Drama and Theatre in Early Modern Europe Ser, 2020)
Half Title -- Series Information -- Title Page -- Copyright Page -- Dedication -- Contents -- Preface -- Figures -- Abbreviations -- Note on Illustrations and the Use of Electronic Resources -- Introduction -- Chapter 1 The Lyon Terence and Its Initial Impact -- 1.1 Contents and mise-en-page -- 1.2 Publishing in Lyon -- 1.3 Composition, Printing, and Distribution -- Chapter 2 Terence's Plays: Commentary and Illustration from Manuscript to Print -- 2.1 Terence as an Educational Classic: Text and Commentary from Antiquity to Medieval and Renaissance Europe -- 2.2 The Development of Manuscript Illustrations of Terence -- 2.3 The Impact of New Learning and Technologies: Donatus and the Advent of Printing -- Chapter 3 The Editor of the Lyon Terence: Jodocus Badius Ascensius -- 3.1 Badius -- 3.2 Early Life and Literary Career to 1493 -- 3.2.1 Flanders and Brabant -- 3.2.2 Italy -- 3.2.3 Lyon -- 3.3 Later Career to 1502 -- Chapter 4 Text and Commentary in Badius' Three Editions of Terence -- 4.1 The 1491 Edition and Donatus -- 4.2 The Lyon Terence: The Commentary of Guy Jouenneaux and Badius' Revisions -- 4.2.1 The Commentary Edition of Guy Jouenneaux -- 4.2.2 Badius' Re-edition of Guy -- 4.3 The 1502 Terence and Its Sources -- Chapter 5 The Illustrative Programme of the 1493 Edition -- 5.1 Badius' Appropriation of the Carolingian Tradition -- 5.2 Gestures in Medieval and Early Modern Culture -- 5.3 Carolingian Gestures -- 5.4 Non-Carolingian Gestures -- 5.4.1 Manly Gestures -- 5.4.2 Female Gestures -- 5.4.3 Affective Gestures -- 5.5 Characterisation through Costuming -- 5.6 Gestures, Illustrations and Commentary Derivative of Donatus in the Lyon Terence -- 5.7 The Illustrator of the Lyon Terence -- Appendix: A Catalogue of Gestures -- Carolingian Gestures -- Non-Carolingian Gestures -- Chapter 6 The Theatricality of the Lyon Terence.